Krisis penggunaan bahasa Jawa krama di generasi muda: Studi kasus pada mahasiswa gen z di kota Malang - Kemala, Ajeng Ayu; Ghozi, Ahmad; Murad, Talhisul; Hidayatullah, Achmad Syahrul; Dewi, Ayunda Lestari (Maliki Interdisciplinary Journal, 2024)
Language is a means for humans to communicate and interact with others which can be found in all corners of the world. In this regard, language is one of the seven universal elements of culture. Not only national and international languages, local languages are also products of the culture itself, one of which is Javanese language spoken by Javanese people. However, there is currently a drastic decline in the use of Javanese language, especially Javanese Krama, among Gen Z or those born between 1997 and 2012. The purpose of writing this scientific article is to find out the intensity of Javanese Krama language use among Gen Z and its causes because the preservation of this regional language is essential so that this kind of phenomenon can be anticipated in the future.